Transitivity Process in Joko Widodo’s Inauguration Speech - Alfrin Juniarto Siringo-ringo; Meisuri Meisuri (Universitas Negeri Medan, 2021)
The thesis deals with Transitivity Process in Joko Widodo’s Inauguration Speech. The objectives of this study were to find out the types of transitivity process used, and to describe transitivity revealed in Joko Widodo’s Inauguration Speech. This study was conducted by using the descriptive qualitative method. The data of the study were the clauses that spoken by Joko Widodo’s in the Inauguration Speech. The data analyzed were taken by listing and tabulating the data. The data were analyzed based on the theory proposed by Halliday’s. The findings indicated that there are transitivity process which consists of six significant types, those are: material, mental, relational, behavioral, verbal, and existential. There are material process is (49,46%), relational process (32,25%), verbal process (6,45%), mental process (5,37%), existential (4,30%), and behavioral (2,15%). The transitivity process reveals that Joko Widodo’s attempts to construct the ideology of democracy during his speech.